2018
DOI: 10.1093/ejcts/ezy150
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular assist device implantation with and without concomitant tricuspid valve surgery: a systematic review and meta-analysis

Abstract: Adding TVS during LVAD implantation is not associated with worse outcome. Adding TVS, nevertheless, may be beneficial, as baseline characteristics of patients undergoing LVAD + TVS were suggestive of a more progressive underlying disease, but with comparable short-term outcome and long-term outcome with patients undergoing isolated LVAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…Similarly, no major changes in the mPAP was observed (35 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] mm Hg in no TVI and 32 [27][28][29][30][31][32][33][34][35][36][37] mm Hg in TVI condition, P ¼ .352). As expected, a statistically significant increase of the CVP was observed from 15 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) mm Hg in no TVI to 26 (24)(25)(26)(27)(28)(29)(30)(31) mm Hg in the TVI condition (P ¼ .020). Furthermore, the CO decreased from 3.2 (1.55-3.7) L/min in no TVI to 2 L/min (1.38-2.8) in the TVI condition (P ¼ .027).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, no major changes in the mPAP was observed (35 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] mm Hg in no TVI and 32 [27][28][29][30][31][32][33][34][35][36][37] mm Hg in TVI condition, P ¼ .352). As expected, a statistically significant increase of the CVP was observed from 15 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) mm Hg in no TVI to 26 (24)(25)(26)(27)(28)(29)(30)(31) mm Hg in the TVI condition (P ¼ .020). Furthermore, the CO decreased from 3.2 (1.55-3.7) L/min in no TVI to 2 L/min (1.38-2.8) in the TVI condition (P ¼ .027).…”
Section: Resultsmentioning
confidence: 99%
“…In the second-stage procedure, severe acute TVI was induced through surgical resection of the TV. All hemodynamic parameters remain stable in the group with LVAD alone or LVAD with TVI except for expected greater CVP value in the TVI group (15 [13-25] mm Hg vs 26 [24][25][26][27][28][29][30][31] mm Hg, P ¼ .020) and lower CO in the TVI group (3.2 [1.55-3.7] L/min vs 2 [1.38-2.8] L/min, P ¼ .027). The increase of CVP was expected as a result from the TV resection.…”
Section: Hr (Bpm) Co (I/min)mentioning
confidence: 97%
“…Severe TR might just reflect the consequences of long‐lasting RV failure and dilatation in patients with HFrEF that might persist despite TVR. The recent meta‐analysis from Veen et al 23 also found that adding a TVR was not associated to differences in term of short or long‐term survival. It, nevertheless, may be beneficial, as baseline characteristics of patients undergoing TVR were suggestive of a more progressive underlying disease.…”
Section: Commentmentioning
confidence: 94%
“…Especially when placing intracorporeal devices in smaller patients, keep the TEE probe in to ensure that at sternal closure the device has not shifted requiring adjustments to keep the IVS midline. Concomitant tricuspid valvuloplasty can be considered in the setting of significant baseline tricuspid regurgitation 20 …”
Section: Medical Management Of Right Heart Failurementioning
confidence: 99%